The Influence of Hedonic Value and Economic Value on Continuance Intention with Satisfaction as an Intervening Variable - Lianto, Fazrian; Dewi, Citra Kusuma; Widodo, Arry; Rubiyanti, Nurafni; Silvianita, Anita (PT FORMOSA CENDEKIA GLOBAL, 2024)
People's behavior towards transportation services has formed new habits in using services for ordering goods and services, especially in terms of ordering ride-hailing services via online-based applications. Gojek, which is one of the most popular ride-hailing applications in Indonesia, is ranked second as the most widely used ride-hailing application in Indonesia. This research aims to determine the influence of Hedonic value and Economic value on the Continuance intention of the ride-hailing application (Gojek), with Satisfaction as an intervening variable. The population in this study are users of ride-hailing services from Gojek in Indonesia, as well as a sample consisting of individuals who meet the criteria for being users of the Gojek application. This research method uses a quantitative approach by applying Smart-PLS analysis.